PETERNAK KAMBING DESA SINDON KECAMATAN NGEMPLAK BOYOLALI - Haryoto Haryoto; Muhtadi Muhtadi; Rusdin Rauf (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
The issue of animal feed and the efficiency of the goat breeding production process, is still a big problem for conventional goat breeders. Therefore, the use of fermented feed technology to save time providing feed, as well as the use of a communal cage system for efficiency and effectiveness in the management of goat farms, needs to be trained and mastered by goat breeders. The purpose of this IbM is to develop the capability of the goat business and increase the yields of goat farmers in the village of Sindon, kec. Ngemplak kab. Boyolali Some solutions offered to help partner problems are (1) introduction and training to goat breeders in Sindon village, Ngemplak district, Boyolali Regency regarding the use of fermented feed technology for integrated management of goat livestock, (2) training and providing technology of leaf counting machines for the production process of fermented feed goat livestock, (3) training and assistance for themanagement of goats by utilizing a communal cage system to increase the efficiency andeffectiveness of the production process. The expected outcome of this IbM activity is to increase the ability of the goat business, increase income and the effectiveness of the goat farming process in Sindon village, Ngemplak district, Boyolali district.AbstrakPermasalahan pakan ternak dan efisiensi proses produksi peternakan kambing, masih menjadi persoalan besar bagi para peternak kambing konvensional. Oleh karenanya, pemanfaatan teknologi pakan fermentasi untuk menghemat waktu penyediaan pakan, serta pemanfaatan sistem kandang komunal untuk efisiensi dan efektifitas dalam pengelolaan peternakan kambing sangat perlu dilatihkan dan dikuasai oleh peternak kambing. Tujuan IbM ini adalah pengembangan kemampuan usaha ternak kambing dan peningkatan hasil budidaya pada peternak kambing di desa Sindon, kec. Ngemplak kab. Boyolali. Beberapa solusi yang ditawarkan untuk membantu permasalahan mitra adalah (1) pengenalan dan pelatihan pada peternak kambing desa Sindon kecamatan Ngemplak Kabupaten Boyolali tentang pemanfaatan teknologi pakan fermentasi untuk pengelolaan ternak kambing terpadu, (2) pelatihan dan pemberian teknologi mesin pencacah dedaunan untuk proses produksi pakan fermentasi ternak kambing, (3) pelatihan dan pendampingan untuk pengelolaan ternak kambing dengan pemanfaatan sistem kandang komunal untuk peningkatan efisiensi dan efektifitas proses produksi. Luaran yang diharapkan dari kegiatan IbM ini adalah peningkatan kemampuan usaha ternak kambing, peningkatan pendapatan serta efektifitas proses budidaya ternak kambing di desa Sindon kecamatan Ngemplak kabupaten Boyolali.